Analysis of Moral Values Embedded in Thengul Puppets Performances - Wintari (International Proceedings of Nusantara Raya, 2023)
Moral values are a guide for individuals to do a good attitude in every action they take. These positive values can come from religious guidance, education, social environment, or other external factors related to a person's daily life. One of these factors is the entertainment and spectacles presenting specific stories with moral values conveyed. This is also found in the performance of Wayang Thengul (Thengul Puppets), which is a distinctive art form in Bojonegoro Regency, East Java. This research is a descriptive-qualitative study aimed at exploring in-depth information about the stories of Wayang Thengul in Bojonegoro from the practitioners of this art form. The research aims to identify the moral values embedded in the stories of Wayang Thengul in Bojonegoro based on the narratives performed in the show. The research findings indicate the presence of numerous stories derived from the Javanese historical story and the Panji tales being performed in Wayang Thengul. These stories contain implicit moral values that encompass teachings of goodness, hard work, perseverance, and determination in the pursuit of happiness.